Efficacy of acupuncture versus sham acupuncture or waitlist control for patients with chronic plantar fasciitis: study protocol for a two-centre randomised controlled trial - Yan Liu; Weiming Wang; Zhishun Liu; Liang Li; Sixing Liu; Zhiwei Zang; Weina Zhang (BMJ Open)
Introduction Plantar fasciitis (PF) is reported to be the most common cause of plantar heel pain. Acupuncture has been used for patients experiencing PF, but evidence of the efficacy of acupuncture on PF is limited. The primary objective of this trial is to compare combined acupuncture and sham acupuncture (SA) versus waitlist control for improving the level of pain experienced by patients suffering from chronic PF.Methods and analysis This will be a two-centre, parallel-group, sham and no-treatment controlled, assessor-blinded randomised trial. We will randomly allocate 120 participants with chronic PF to acupuncture, SA and waitlist control groups at a ratio of 2:1:1. Participants in the acupuncture and SA groups will receive a 30 min acupuncture or SA treatment for a total of 12 sessions over 4 weeks, with a 12-week follow-up. Participants in the waitlist control group will not undergo treatment for a period of 16 weeks but instead will have the option of 4 weeks (12 sessions) of acupuncture free of charge at the end of the follow-up period. The primary outcome will be the treatment response rate 4 weeks after randomisation, assessed as a minimum of 50% improvement in the worst pain intensity during the first steps in the morning compared with the baseline. All analyses will be performed with a two-sided p value of <0.05 considered significant following the intention-to-treat principle.Ethics and dissemination The study has been approved by the Ethical Committee of the Guang’anmen Hospital, China Academy of Chinese Medical Sciences (approval no. 2019-210-KY). The results will be disseminated through presentation at a peer-reviewed medical journal, the relevant conferences and scientific meetings.Trial registration NCT04185259.